**Examples of Homogeneous Differential equations**

- dy/dx = x(x - y)/y
^{2}
- dy/dx = (x + y)/(x - y)
- dy/dx = (x
^{2} + y^{2})/xy
- dy/dx = (x
^{3} + y^{3})/(xy^{2} + yx^{2})

**Solving a Homogeneous Differential Equation**

The general solution of a homogeneous differential equation is calculated by integrating the given differential equation.

A homogeneous differential equation: dy/dx = f(x, y) is solved by separating the variable and its derivative on either side, then integrating it with respect to the variable.

**Note:** The equation for the homogeneous differential equation does not include a constant term. A constant term exists in the linear differential equation. The solution for a linear differential equation is possible if the constant term is removed from the equation and is transformed into a homogeneous differential equation.

General steps to solve a homogeneous differential equation includes:

- We use the substitution y = v.x to solve a homogeneous differential equation of the type dy/dx = f(x, y). This replacement makes it simple to integrate and solve.
- The differentiation of y = vx, with respect to x, gives dy/dx = v + x.dv/dx.

3. By substituting the value of dy/dx in the expression dy/dx = f(x, y) = g(y/x) we get:

v + x.dv/dx = g(v) , where v = y/x.

4. Separating the variables v and x, we get:

5. Integrate LHS and RHS,

6. The general solution of the given homogeneous differential equation is

To obtain the general solution of the homogeneous differential equation, we replace the value of v = y/x. The inclusion of +C in the solution indicates that it is a general solution. By solving and substituting the value of +C, we can obtain the particular solution to the given homogeneous differential equation.

Letâ€™s understand with an example,

Q: Solve the below-mentioned differential equation.

Solution:

- Try to make y/x terms.

2. Now we have a function of y/x.

3. Now use Separation of Variables:

4. Substitute v = y/x

Hence Solved.

**Also, Try Solving:**

- dy / dx = y*( x - y ) / x
^{2}
- dy / dx = ( x - y ) / (x + y)
- dy / dx = ( 3x + 2y ) / 3y
- xCos(y/x)*dy / dx = y*Cos(y/x) + x

**Frequently Asked Questions**

**1. What is a homogeneous differential equation?**

A homogeneous differential equation contains a set of variables with differentiation and a function. In a homogeneous differential equation, the function f(x, y) is a homogeneous function such that f(Î»x, Î»y) = Î»nf(x, y) for any non-zero constant n.

**2. Why is it called a homogeneous equation?**

A linear differential equation Ly = f with some function f = 0 is called a homogeneous equation because if x is a solution of Lx = 0, then kx also solves this equation for some constant k.

**3. How can we prove a differential equation to be homogenous?**

To prove a differential equation to be homogenous, show that it is of the form f(Î»x, Î»y) = Î»^{n}f(x, y) for any non zero constant Î».

**Conclusion**

In this article, we learned about Homogeneous differential equations. We learned that homogeneous differential equations are of the form f(Î»x, Î»y) = Î»nf(x, y) for any non zero constant Î».

We also learned about the steps required to solve a homogeneous differential equation.

Now you are all set to solve any level of the homogeneous differential equation.

You can use __Coding Ninjas Studio__ to practice various DSA questions asked in the interviews. It will help you in mastering effective coding techniques, and you will also get __interview experiences__ with people working in big companies.